Análise da implantação de reservatórios de amortecimento de cheias e de aproveitamento de água pluvial em lotes urbanos - Lima Neto, Vicente de Sousa (2021)
With the waterproofing of watersheds, components of the water balance are modified, with increased runoff and decreased infiltration. As a result, urban floods occur with greater frequency and magnitude, changing the natural logistics of the environment and causing economic losses, pollution, health problems, traffic interruptions, and human losses. Therefore, this study aimed to analyze the effects of the implementation of reservoirs in urban lots acting on the damping of floods and the use of rainwater, installed in the Mirandão neighborhood, city of Crato, state of Ceará, Brazil. The first stage of the methodology consisted in the dimensioning of an urban micro drain network in the UFC System and hydrodynamic simulations in the SWMM with and without reservoirs, to evaluate hydrographs from the contribution basins, flows, and water slides conducted in the galleries, flows, and volume drained in the outlets. In the second stage, the reservoirs were dimensioned according to the methods present in NBR 15527/2007 and compared with a simulation in the SWMM to verify the volume acting on the damping of floods and the use of rainwater. Finally, several catchment areas and non-potable water demand scenarios were carried out to determine the volume of the reservoir. The results of the first stage showed that the reservoirs were able to reduce peak flows in sub-basins and galleries on average with maximum values of 83% and 71%, respectively, and 52% of the maximum relative water depth in the galleries. The drained volume and peak flow in the outlets had a maximum reduction of 68% and 69%, respectively. The results of the second stage indicated that the reservoir volumes, acting on the use of rainwater, are directly proportional to the demands for non-potable water for certain methods, and in some scenarios, they would meet the use, but not the damping. Therefore, the reservoirs in the lots proved to be efficient in decreasing peak flows and volumes drained in the sub-basins, galleries, and outlets, enabling better management of the water balance of the hydrographic basin, with a reduction in the occurrence of floods in the area itself downstream. Besides, drainage systems can be designed with lower flow rates and stored water can be used for non-potable uses.